Restorative Justice in Settlement of the Crime of Land Grabbing at the East Kupang Sector Police - Daniel imanuel nguru; Ishak Alfred Tungga; A Resopijani (Indonesian Journal of Contemporary Multidisciplinary Research, 2023)
Conflicts related to land will never end, the existence of land is very valuable and important. Making land grabbing cases rife, the number of land grabbing cases the last few years increases, so that from the East Kupang Sector Police there is a need for alternative case resolutions outside the judicial process that are able to bring back hope of the value of justice in society, such as restorative justice or restorative justice. However, of the 8 cases handled by the East Kupang Sector Police, only 1 case was able to carry out restorative justice, the formulation of this research problem is: (1) How is restorative justice in solving land grabbing crimes in the East Kupang Sector Police? (2) What are the obstacles to restorative justice in solving land grabbing crimes in the East Kupang Sector Police? This research is empirical research. The aspects studied are (1) Application of restorative justice in the Settlement of Land Seizure Crimes at the East Kupang Police Station and (2) Restorative justice Obstacles in the Settlement of Land Seizure Crimes at the East Kupang Police Station